MIX BERRIES ICE CREAM BERBASIS BLACKBERRY, RASPBERRY DAN MULBERRY ALTERNATIF MAKANAN TINGGI ANTIOKSIDAN DAN ANTOSIANIN - Surmita Taufik; Widartika Widartika (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
Free radicals in the body can be produced endogenously and exogenously. Free radicals can cause adverse health effects such as cell damage and premature aging. Ice cream is a food that having good tastes. Blackberry (Rubus sp.), Raspberry (Rubusidaeus L.) and Mulberry (Morus Alba R.) are fruits that contain polyphenolic compounds such as anthocyanins and are rich in antioxidants. The antioxidant properties of these fruits can absorb oxygen radicals to fight perosokil radicals, hydrogen peroxide, superoxide, singlet oxygen, and hydroxyl radicals. This study aims to determine the effect of adding blackberries, raspberries and mulberries to the organolpetic properties, antioxidant levels and anthocyanins of mix berries ice cream. The addition of blackberries, raspberries and mulberries was made in 3 formulas, namely 40 grams (Formula 1), 30 grams (Formula 2) and 20 grams (Formula 2) grams into 100 grams of ice cream ingredients. From the results of the statistical test above, it can be concluded that there is an effect of adding blackberries, raspberries and mulberries to the taste and color (p value <0.05) and there is no effect of adding blackberries, raspberries and mulberries to the aroma and texture of the snack bar (p value> 0 ,05) mix berries ice cream. Formula 1 with the addition of mixed berries has more advantages in terms of taste, aroma and texture, antioxidant and anthocyanin content.